The Effectiveness of Motivation Training for Increasing Studentsâ Motivation - Tentama, Fatwa (Universitas Ahmad Dahlan, 2014)
AbstractStudentsâ low level of motivation becomes a matter of concern to be addressed immediately. Students motivation needs to be improved as it is a factor that will affect their lives in the future. This study aims to observe or examine the effectiveness of motivation training in increasing students motivation. The research method used was the pre-experiment with one group pre-test post-test design. The subjects of this study were 15 boy and girl students of Grade X of SMK who had a low level of motivation. The measuring instruments were the motivation scales given during the pre-test and post-test. The quantitative data were statistically analyzed using the Wilcoxon test with non-parametric measurements to determine the significance of difference in the motivation level before and after the training. The data were tested using SPSS 17.0 for Windows. The result of Wilcoxon analysis to test the hypothesis whether there is a difference between the pre-test and post-test of students motivation showed that the p = 0.025 (p < 0.05). This means that there was a significant difference between the motivation before the treatment (pre-test) and after the treatment (post- test), which indicated that the students motivation increased after a treatment in the form of motivation training.Keywords: motivation training, motivation